2004
DOI: 10.1091/mbc.e04-03-0188
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Membrane Proteins Contain Common Pex19p-binding Sites that Are an Integral Part of Their Targeting Signals

Abstract: Targeting of peroxisomal membrane proteins (PMPs) is a multistep process that requires not only recognition of PMPs in the cytosol but also their insertion into the peroxisomal membrane. As a consequence, targeting signals of PMPs (mPTS) are rather complex. A candidate protein for the PMP recognition event is Pex19p, which interacts with most PMPs. However, the respective Pex19p-binding sites are ill-defined and it is currently disputed whether these sites are contained within mPTS. By using synthetic peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
197
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(206 citation statements)
references
References 47 publications
8
197
0
1
Order By: Relevance
“…How peroxins target to peroxisomes is unclear, although several, such as Pex13 and Pex11, are targeted by binding to Pex19 and Pex3 (25). Yet a Pex13 mutant unable to bind Pex19 is imported into peroxisomes (26), suggesting the existence of multiple importation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…How peroxins target to peroxisomes is unclear, although several, such as Pex13 and Pex11, are targeted by binding to Pex19 and Pex3 (25). Yet a Pex13 mutant unable to bind Pex19 is imported into peroxisomes (26), suggesting the existence of multiple importation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a consensus sequence for recognition of a protein by Pex19p has been defined (21). Two putative Pex19p recognition sequences were identified in Pex30p at amino acids 24 -38 and 97-111 (Fig.…”
Section: The Pex19p Recognition Sites In Pex30p and Pex32p Do Not Ovementioning
confidence: 99%
“…The direct insertion of PMPs into the peroxisomal membrane is facilitated by Pex19p, a peroxin that is localized predominantly to the cytosol and to a much lesser extent at the surface of peroxisomes (17)(18)(19). Pex19p interacts essentially with all PMPs via a consensus motif that is found at least once in a PMP (20,21). The interaction of Pex19p and a PMP could either prevent the aggregation of the PMP or serve to guide the PMP to the peroxisomal membrane.…”
mentioning
confidence: 99%
“…Neurospora PEX3 enlists PEX19, a farnesylated cytosolic protein, to chaperone nascent PMPs to PEX3 for membrane insertion (Chen et al, 2014). Yeast PMPs bind PEX19 via a membrane peroxisome-targeting signal, a hydrophobic motif near the transmembrane domain (Rottensteiner et al, 2004); similar sequences are found in plant PMPs (Nyathi et al, 2012).…”
Section: Peroxisome Genesis Membrane Protein Insertion and Budding Frmentioning
confidence: 99%